Philo and the church fathers : a collection of papers - Runia, David T. (Vigiliae Christianae, Supplements, 1995)
The extensive writings of the Jewish philosopher and exegete Philo of Alexandria (15 BCE to 50 CE) were preserved through the efforts of early Christians, who decided that these works could assist them in developing their own distinctive kind of thought. The present collection of papers, written from 1989 to 1994, is published as a companion volume to the author's monograph Philo in Early Christian Literature: A Survey (1993). The papers deal with various aspects of the process of reception that Philo received at the hands of the Church Fathers. Authors who are given particular attention are Athenagoras, Clement, Origen, Basil, Gregory of Nyssa, Isidore of Pelusium and Augustine. The papers also include a hitherto unpublished English translation of the author's inaugural lecture held at Utrecht in April 1992.